Research on the Influence of Sensor Network Communication in the Electromagnetic Environment of Smart Grid - Yiying Zhang; Suxiang Zhang; Yuemin Ding (Journal of Electrical and Computer Engineering)
Smart grid adopts wildly various sensors for lots of applications to sense work environment, monitor production process and realize the automation control, and so forth. However, due to the wireless and open communication, the electromagnetic phenomena in the communication and the electric network of the sensor network usually produce the mutual interference. Meanwhile, electrical equipment and sensors are usually in high pressure electromagnetic environment. Therefore, it is very necessary and important to ensure the reliability and stability in smart grid applications. And the sensing and communication device must be after equal parameter simulation environment under strict evaluation and verification can be put to use in actual production operation system. In this paper, we analyze the application of wireless sensor network in smart grid and propose the test method of the interaction between WSN and smart grid.